Comparing post-traumatic stress disorder (PTSD) in primiparous and multiparous women with preeclampsia - Zahra Abedian; Narges Soltani; Naghmeh Mokhber; Habibollah Esmaeily (Mashhad University of Medical Sciences, 2013)
Background and Aim: Post-Traumatic Stress Disorder is one of the anxiety disorders which occur in postpartum period. The prevalence of PTSD - induced by preeclampsia has been already reported as 28%, however no study was found to compare PTSD in primiparous and multiparous women. This study was therefore conducted to compare PTSD in primiparous and multiparous women. Methods: This comparative descriptive study was performed on 100 pregnant women with preeclampsia including 56 primiparous and 44 multiparous women who selected conveniently from labor wards of university hospitals in Mashhad, Iran in 2012. PTSD was diagnosed by psychiatrist interview and Perinatal Post-traumatic stress Questionnaire (PPQ) in 6th week postpartum. Social support was measured using Hopkins questionnaire in 2nd and 6th week postpartum. Data analyzed with SPSS Version 16 using Spearman correlation coefficient and Mann-Whitney test. Results: The rate of PTSD was 24% in primiparous and 37.8% in multiparous women. There was no significant difference in relation to mean score of PTSD in primiparous and multiparous women. Mean score of social support in 2nd and 6th week postpartum was significantly higher in primiparous women (P=0.000). 34% of multiparous vs. 5.4% of primiparous women had unwanted pregnancy (P=0.000). There was also a direct relationship between postpartum social support in 2nd (P=0.005) and 6th week  postpartum (P=0.002) and the rate of PTSD. Conclusion: The rate and mean score of PTSD in multiparous has been higher than primiparous women. Thus, it seems that multiparous women are at higher risk for PTSD due to lower postpartum social support and higher rate of unwanted pregnancy.